Need of Sociolinguistic Study in Nepal (The Journal of Knowledge and Innovation, 2024)
Nepal has a rich linguistic and cultural heritage. Our language has such a linguistic property than no other so called developed languages possess. Historically, we belong to rich language families. Linguistically, 168, 340 people remain in dark. Even most of the identified languages are struggling for existence. Can we compensate at any way if the two Sadhani speakers die? Are we ready to tolerate the blame for being observer and doing nothing? This is an important social issue today. The responsibility of our generation to the future of our country is serious and decisive. The intention of my article is to set the stage for further discussion and make aware of this issue seriously.